تحرِي العلاقة بين درجة اللابؤرية وعدد خلايا بطانة القرنية ونسبة الخلايا السداسية في هذه البطانة - سليمان, يوسف محمد (Latakia University Journal -Medical Sciences Series, 2019)
1- الهدف: تحديد العلاقة بين درجة اللابؤرية من جهة وبين تعداد خلايا بطانة القرنية ونسبة الخلايا السداسية من جهة ثانية. 2- مواد و طرائق البحث: 88 شخص (176عين) أجري لهم فحص تعداد خلايا بطانة القرنية و نسبة الخلايا السداسية لهم بجهاز Endothelium Mic. Non contact, Specular Microscope, Italy غير التماسي، بعد أن استبعدت حالات القرنية المخروطية والأمراض العينية الأخرى غير اللابؤرية. 3- النتائج: تراوحت أعمار المرضى بين 7-75 سنة (المتوسطٍ= 26±12.2 والوسيط= 22 سنة)، وتراوحت درجة اللابؤرية ما بين 5.0-0.25 كسيرات سالبة بمتوسطٍ= 0.81937±0.9219, أما تعداد خلايا بطانة القرنية فقد بلغ مابين 3729-1903 خلية بمتوسطٍ= 352.42±2834 وكانت نسبة الخلايا السداسية متراوحة بين 33-83% (المتوسط 58.1±80.253%). بالتحليل الإحصائي تبين أن العلاقة بين درجة اللابؤرية وتعداد خلايا بطانة القرنية ونسبة الخلايا السداسية ذات دلالة إحصائية هامة (P=0.000). 4- الخلاصة: ينخفض عدد خلايا بطانة القرنية وتنقص نسبة الخلايا السداسية بالتصاعد المتزايد لدرجة اللابؤرية. 1. Objective: To determine the relationship between the degree of astigmatism and between the count of corneal endothel-cells and the proportion of hexagonal-cells. 2. Materials and methods: A total of 88 patients (176 eyes) were screened for the the count of corneal endothel-cells and the proportion of hexagonal cells with Endothelium Mic. Non contact, Specular Microscope, Italy Unsatisfactory, having excluded keratoconus cases and other non-astigmatic diseases. 3. Results: Patients ranged in age from 7 to 75 years (mean 26 ± 12.2 and median 22 years). The astigmatism ranged from 0.25-5.0 negativ dioptries with an average of 0.81937 ± 0.9219. The count of corneal endothel-cells was between 1903-3729 cells with an average of 352.42 ± 2834, and the proportion of hexagonal cells ranged between 33-83% (mean 58.1 ± 8.253%). Statistical analysis showed that the relationship between the degree of astigmatism and the the count of corneal endothel-cells and the proportion of hexagonal cells have significant statistical significance (P = 0.000). 4. Conclusion: The number of the count of corneal endothel-cells decreases and the proportion of hexagonal cells decreases with the increasing of degree of astigmatism.